HCV, HIV AND HBV rapid test diagnosis in non-clinical outreach settings can be as accurate as conventional laboratory tests - Muñoz-Chimeno, Milagros; Valencia, Jorge; Rodriguez-Recio, Alvaro; Cuevas, Guillermo; Garcia-Lugo, Alejandra; Manzano, Samuel; Rodriguez-Paredes, Vanessa; Fernandez, Beatriz; Morago, Lucía; Casado, Concepción; Avellón, Ana; Ryan, Pablo (Scientific reports, 2023)
Point of care rapid diagnostic tests (POC-RDT) for Hepatitis C virus (HCV), Human Immunodeficiency virus (HIV) and Hepatitis B virus (HBV), are ideal for screening in non-clinical outreach settings as they can provide immediate results and facilitate diagnosis, allowing high risk population screening. The aim of this study was to compare POC-RDT with laboratory conventional tests. A total of 301 vulnerable evaluable subjects (drug users, migrants and homeless population) were recruited at a mobile screening unit in outreach settings in Madrid. Fingerprick whole blood capillary samples were tested using the SD BIOLINE HCV POC-RDT, Determine HIV Early Detect and Determine HBsAg 2, and the results were assessed against the LIAISON XL HCV, HIV and Murex-HBsAg-Quant, reference assays, respectively. The feasibility and user satisfaction of the POC-RDT were evaluated through a questionnaire. The resolved sensitivity and resolved specificity and their 95% confidence intervals (95% CI) were as follows, respectively: SD-BIOLINE-HCV: 98.8% (95% CI 93.4, 100.0) and 100.0% (95% CI 98.3, 100.0); Determine HIV Early Detect: 100% (95% CI 85.2, 100.0) and 100% (95% CI 98.7, 100); and Determine HBsAg 2: 66.7% (95% CI 9.4, 99.2) and 100.0% (95% CI 98.7, 100.0). As expected, the number of subjects with a confirmed positive result for HBsAg was very low (n = 4). Therefore, the analytical sensitivity has been evaluated in addition: The Determine HBsAg 2 test demonstrated 100% sensitivity for standard concentrations ≥ 0.125 IU/mL. The subject questionnaire yielded positive feedback for most subjects. The POC-RDT fingerprick blood collection method was well received, and the tests demonstrated a comparable clinical performance with conventional tests in outreach settings and vulnerable high-risk populations.